Managing the Repertoire: Stories, Metaphors, Prototypes, and Concept Coherence in Product Innovation - Seidel, Victor P.; O’Mahony, Siobhán (Organization Science, 2014)
Arecognized challenge in innovation scholarship is how to coordinate the efforts of many minds contributing to the design of a single artifact. Much research shows that product concept representations can help coordinate design tasks, but we know little about the practices that make representations more or less effective. We used an inductive approach to examine how six teams in three industries used concept representations when creating novel products. All six teams crafted three types of representations: stories, metaphors, and prototypes. However, merely using representations did not ensure a shared repertoire and concept coherence—a common understanding of desired product attributes. Teams that failed to consistently engage in three practices—(1) collective scrutiny of representations, (2) linking representations to design constraints, and (3) active editing of representations—produced concept disunity, with disparate understandings of desired product attributes. Teams that maintained concept coherence were better able to coordinate design tasks than teams that experienced concept disunity. Our research explains how the ultimate effect of concept representations on the coordination of innovation is contingent on the practices used to manage a repertoire of representations in use.